Comparison of feed-in tariffs and tenders to remunerate solar power generation. - Grau, Thilo (My University, 2014)
This paper analyzes the trade-offs for using feed-in tariffs or tenders to remunerate different scales of solar photovoltaics (PV) projects. In recent years, European countries increasingly combined feed-in tariffs for small renewables systems with tenders for large installations. This study develops an analytic framework to quantify deployment effectiveness of responsive feed-in tariff adjustment mechanisms across project scales and to compare specific cost effectiveness factors of feed-in tariffs and tenders for PV plants with their dynamic cost trends. To assess deployment effectiveness, an analytic model is used to simulate installations and feed-in tariffs for different project sizes. Then semi-structured interviews with German and French project developers are conducted to identify additional factors to be considered for a comparison of feed-in tariffs and tenders, and to explore how different remuneration schemes impact cost of capital and transaction costs. The paper finally discusses the relative merits of feed-in tariffs and tenders.
Keywords: Energie; Subvention; Förderungsprogramm; Fördermittel; Energieproduktion; Sonnenenergie; Solaranlage; Erneuerbare Energie; Photovoltaik; Politikinstrument; Erneuerbare-Energien-Gesetz